Proceso de Adaptación Cultural de un grupo de Inmigrantes Venezolanos llegados en los último 5 años en la Ciudad de Buenaventura Valle del Cauca (2024)
The objective of this research was to investigate the process of cultural adaptation of a group of Venezuela migrants who arrived in the last 5 years to the city of Buenaventura, Valle del Cauca. To address this objective, the definition of the cultural adaptation process was taken into account in the theoretical framework. According to Vargas (2016), two types of migración are defined: forced and voluntary, while Berry (1992) describes four cultural adaptation strategies: separation, integration, assimilation and marginalization. Likewise, Pichón R (1966) divides adaptation into two processes: active and passive. To develop this research, a qualitative methodology with a phenomenological design was used. To collect the data that allowed the analysis, a semi-structured interview was conducted with three subjects, who are Venezuelan migrants who arrived in the city of Buenaventura in the last 5 years. Finally, it is concluded that a process of active cultural adaptation has been achieved, achieving assimilation and integration while maintaining their culture of origin, in the context of voluntary and forced migration.